2022
DOI: 10.1111/1759-7714.14398
|View full text |Cite
|
Sign up to set email alerts
|

Association between clinical outcomes and local treatment in stage IV non‐small cell lung cancer patients with single extrathoracic metastasis

Abstract: Background: Local treatment (LT) such as radiotherapy and metastasectomy on metastatic sites may improve outcomes in oligometastatic NSCLC patients, but more data are necessary to support LT in oligometastatic diseases. Patients with single extrathoracic metastatic lesion are more likely to benefit from local therapy. In this study, we evaluated the impact of LT in NSCLC patients with a single extrathoracic metastatic lesion. Methods: Data were obtained from the Korean Association for Lung Cancer Registry (KAL… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 57 publications
(115 reference statements)
1
1
0
Order By: Relevance
“…Several retrospective studies also analyzed prognostic factors in OMD patients. A reduced performance status, comorbidity and sex were identified as poor prognostic factors in other studies as well as in the present study [ 37 , 38 , 39 ]. Negative prognostic factors such as poorer performance status and severe comorbidity did not only influence prognosis but could also decrease treatment tolerance [ 40 ].…”
Section: Discussionsupporting
confidence: 78%
“…Several retrospective studies also analyzed prognostic factors in OMD patients. A reduced performance status, comorbidity and sex were identified as poor prognostic factors in other studies as well as in the present study [ 37 , 38 , 39 ]. Negative prognostic factors such as poorer performance status and severe comorbidity did not only influence prognosis but could also decrease treatment tolerance [ 40 ].…”
Section: Discussionsupporting
confidence: 78%
“…Chen et al enrolled a total of 29 patients with EGFR -mutant advanced lung adenocarcinomas who also underwent surgical resection; the median PFS after surgery was 36.4 months, and the median OS was still not reached [ 27 ]. In Korea, Lim et al conducted a study supported by the Korean Central Cancer Registry and the Lung Cancer Registration Committee, which showed that patients who underwent LCT had significantly better OS than those who did not (HR [95% CI]: 0.448 [0.242–0.829], p = 0.011) [ 36 ]. In China, Kuo et al examined patients with NSCLC associated with driver gene mutations who were treated with targeted therapy, followed by salvage therapy, resulting in significantly longer PFS than in those treated with targeted therapy alone (median PFS: 23.4 vs. 12.9 months, p = 0.0004) [ 37 ].…”
Section: Discussionmentioning
confidence: 99%